Enhancing Early Childhood Numeracy: The Impact of Abacus Activities at the Bali Abacus House Guidance Institute - Ni Ketut Erawati; Hapidin Hapidin; Sri Wulan (STAI Hubbulwathan Duri, 2025)
This study explores the implementation, opportunities, challenges, and influencing factors of numeracy skill development in children aged 5–6 years through abacus activities at the Bali Abacus House tutoring institution. A qualitative case study approach was used, involving 15 children, parents, and teachers over six months. Data were collected through observations, interviews, and document analysis. Triangulation techniques ensured accuracy and validity by cross-verifying information from multiple sources. Findings indicate that abacus activities provide a strong foundation for counting and mathematical concept development. Opportunities include improved arithmetic understanding, while challenges involve the need for trained instructors and children's transition from concrete to abstract mathematical thinking. The success of abacus learning is influenced by developmentally appropriate teaching methods, such as Montessori-based individualized learning. However, integrating abacus activities into different educational settings presents challenges, particularly with the increasing emphasis on digital literacy in modern curricula. Balancing hands-on learning with digital tools is crucial to maintaining engagement and effectiveness. Incorporating abacus activities into early childhood education can enhance cognitive processing and numeracy skills. A blended approach that integrates abacus-based learning with digital resources may optimize outcomes. Future research should examine the long-term impact of abacus training on mathematical proficiency and explore strategies for its integration into diverse educational models.